Apple polyphenol extract improves insulin sensitivity in vitro and in vivo in animal models of insulin resistance. Issue 1 (December 2016) - Manzano, Manuel; Giron, María; Vilchez, José; Sevillano, Natalia; El-Azem, Nuri; Rueda, Ricardo; Salto, Rafael; Lopez-Pedrosa, Jose
Abstract Background Apple polyphenols could represent a novel nutritional approach in the management and control of blood glucose, especially in type 2 diabetics. The aim of this study was to test the therapeutic potential of an apple polyphenol extract (APE) in an insulin-resistant rat model and to determine the molecular basis of insulin sensitivity action in skeletal muscle cells. Methods Acute effect of APE on the postprandial hyperglycemic response was assayed in 15 week old obese Zucker rats (OZR), by using a meal tolerance test (MTT). The ability of APE to improve whole peripheral insulin sensitivity was also assayed in a chronic study by using the euglycemic-hyperinsulinemic clamp technique. To elucidate the molecular mechanisms, rat L6 myotubes were used. Glucose uptake was measured by using 2-[3H]-Deoxy-Glucose (2-DG) and specific inhibitors, as well as phosphorylation status of key kinases, were used to determine the implicated signaling pathway. Results In vivo study showed that nutritional intervention with APE induced an increase of insulin sensitivity with an increase of glucose infusion rate (GIR) of 45 %. Additionally, in vitro results showed a synergistic effect between APE and insulin as well as increased glucose uptake through GLUT4 translocation in muscle cells. This translocation was mediated by phosphatydil inositol 3-kinase (PI3K) and peroxisome proliferator-activated receptor-gamma (PPARγ) signaling pathways. Conclusions As a whole, this study describes the mechanisms involved in the insulin sensitizing effect of APE, which could be considered a promising ingredient for inclusion in nutritional products focused on the management of chronic diseases such as diabetes.